Eros and Psyche: Apuleius Skewed - Meintani, Anastasia (Archäologischer Anzeiger, 2023)
A unicum in the corpus of coroplastic production – a terracotta group from Egypt – is exhibited in a case in the Benaki Museum in Athens. Whereas what is depicted is quite straightforward, a distorted version of Eros and Psyche, the actual identity of the figures represented is less so. Semeli Pingiatoglou in thoroughly publishing the piece identifies them as mime actors. In this paper, a different interpretation is offered: it is based, on the one hand, on the characteristics of the Eros iconography, and on the other, on what is (un-)known about mimes.